Integration of the STEAM Approach Based on Islamic Values in Pesantren Education: An Exploratory Case Study Grounded in Project-Based Learning and the Principles of Ta’dib - Pepilina, Dini; ⁠Fauzi, ⁠Fauzi; Safitri, Ani; Aminudin S, Muh. Dzihab; Sari, Selly Nurlela (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2025)
Purpose – This study aims to explore the implementation of the STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach based on Islamic values in pesantren, as a response to the need for integrating modern scientific knowledge and Islamic spirituality in addressing 21st-century challenges. The focus of the study is to identify contextual strategies for implementing STEAM, analyze students' responses to the integration of Islamic values within STEAM learning, and formulate a conceptual framework for STEAM integration grounded in the principles of Islamic education (ta’dib). Design/methods/approach – This study employs a qualitative approach through an exploratory case study design at Pondok Pesantren Tahfidzul Qur’an Al Husna Bukit Rajawali. Data were collected through participatory observation, semi-structured interviews with five key informants (teachers, pesantren leaders, students), and document analysis conducted during March 2025. Data analysis was carried out thematically using triangulation techniques to validate the findings. Findings – The results indicate that STEAM was implemented through project-based learning, including projects such as constructing a natural water filter, producing educational videos, and creating Islamic geometry-based calligraphy. The integration of Islamic values was carried out substantively, with explicit connections between STEAM activities and Qur’anic verses and hadiths, significantly enhancing students' enthusiasm and active engagement. Identified challenges include limited learning facilities and teachers’ competencies in applying interdisciplinary learning. Research implications – Practically, this study recommends that pesantren improve teachers' pedagogical competencies through regular training in STEAM methodologies and invest in simple laboratory facilities or collaborative learning spaces. This integration model can be implemented in other pesantren with similar characteristics to enhance the quality of Islamic education in preparing a generation that is characterized, religious, and capable of addressing global challenges.